Romania : Staff Report for the 2012 Article IV Consultation, Sixth Review Under the Stand-By Arrangement, and Requests for Waiver of Nonobservance of Performance Criterion and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2012)
Significant progress has been made in macroeconomic stabilization under two successive SBAs but the economic recovery remains fragile. Growth is expected to remain subdued in the near term and to only gradually recover over the medium term, with risks to the outlook mostly on the downside. With strong trade and financial sector linkages, Romania is exposed to the euro area crisis. Fiscal and external reserves provide a buffer and the banking sector remains well-capitalized. At the same time, the political situation has become more unsettling with three governments in 2012, uneasy cohabitation between the President and the governing coalition that has sought to remove him, and parliamentary elections to be held in the fall. The political uncertainty has contributed to accelerated exchange rate depreciation and higher financing costs, and has dented confidence.